Effect of temperature on the preferential intergranular oxidation susceptibility of thermally-treated Alloy 600. (October 2022) - Volpe, L.; Bertali, G.; Scenini, F.; Burke, M.G.
Abstract: Thermally-treated Alloy 600 coupons were tested in pressurized water reactor simulated primary water at 320 °C and in high-pressure superheated steam at 400 °C to study the effect of a "semi-continuous" network of intergranular carbides on the stress corrosion cracking "precursors events": preferential intergranular oxidation (PIO) and diffusion-induced grain boundary migration (DIGM). The intergranular carbides were partially consumed due to the environmental exposure, whereby the Cr released from the carbides contributed to the formation of the external oxide layer that limited both PIO and DIGM. The results were compared with previous studies in which similar coupons were exposed to H2 -steam. Highlights: Thermally-treated Alloy 600 was exposed to PWR simulated primary water and high pressure steam. Thermally-treated Alloy 600 is susceptible to intergranular oxidation. The intergranular Cr-rich M7 C3 carbides were susceptible to decomposition Carbide decomposition provides Cr for the formation of a dense surface Cr2 O3 . The oxidation behaviour is comparable to that observed in superheated H2 -steam.